ANALISIS KEPUASAN DAN LOYALITAS KONSUMEN JAMU GENDONG DI KOTA SUKABUMI - Djamaludin, Moh. Djemdjem; Sumarwan, Ujang; Mahardikawati, Gustia Nur Aria (Jurnal Ilmu Keluarga dan Konsumen, 2009)
The purpose of this study were to analyze satisfaction and loyalty of traditional medicinal herbs consumer in Sukabumi. This study used the concept of traditional approach analysis and brand loyalty. The data were collected from February to March 2008 in Sukabumi. Frequency and descriptive statistics were used to analyze the single variable. Cross tabulations and Chi Square were utilized to examine the relationships between two variables. Factor analysis were used to analyze multivariate. The results of study showed that consumers of traditional medicinal herbs in Sukabumi feel satisfied in many attributes, both product and service. Most consumers had enough loyalty index that is 23,3. There were significant relationships between characteristics of costumer (marriage status, education, and income) and satisfaction that are consist of six factors (hygiene, characteristic of product, characteristic of traditional medicinal herbs peddler, color of medicinal herbs and medicinal peddler service, friendliness and responsiveness, and marketing mix). Marketing strategy that suggest to increase number of selling traditional medicinal herbs are keeping fresh and hygiene, labeling names of traditional medicinal herbs in every bottles, maintaining price, using word of mouth promotion, using vehicle for distribution (ex: motorcycle or bicycle), and organizing selling location.